Impact d’une tâche monologale ou dialogale sur le traitement de l’implicite relatif à l’ethos du locuteur dans un débat - Bernadeta Wojciechowska (Corela)
An impact of a monologue and a dialogue task on the treatment of the speaker’s implicit ethos in a radio polemical debateThis research focuses on the development of the French philology students’ skills to assess the expertise of the speakers in the radio debate. The proposed study is based on the discourse analysis and the rhetorical argumentation approach and it considers the didactic exploitation of the concept of ethos. The capture and processing of ethos by students are studied in two tasks: 1) monologue: an individual response in writing and 2) dialogue: a discussion in pairs. The comparison of students’ production in both didactic situations allows to capture their impact on the way of perceiving and clarifying the implicit data concerning ethos.